2001
DOI: 10.1037/0021-843x.110.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Postdisaster stress in the United States and Mexico: A cross-cultural test of the multicriterion conceptual model of posttraumatic stress disorder.

Abstract: Data on symptoms of posttraumatic stress disorder (PTSD) were collected 6 months after Hurricanes Paulina (N = 200; Mexico) and Andrew (non-Hispanic n = 270; United States) using the Revised Civilian Mississippi Scale. A 4-factor measurement model that represented the accepted multicriterion conceptualization of PTSD fit the data of the U.S. and Mexican samples equally well. The 4 factors of Intrusion, Avoidance, Numbing, and Arousal correlated significantly and equivalently with severity of trauma in each sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
90
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 26 publications
4
90
2
Order By: Relevance
“…It is possible that individuals in these communities may have suffered greater psychological problems due to fewer economic resources and greater job instability (Thiel de Bocanegra and Brickman, 2004). There may also be cultural differences in the desirability of reporting psychiatric symptoms that could affect the ethnicity-PTSD relationship (Norris et al, 2001), which we did not explore. We also did not have predisaster data, with much of our data being based on retrospective measures.…”
Section: Discussionmentioning
confidence: 90%
“…It is possible that individuals in these communities may have suffered greater psychological problems due to fewer economic resources and greater job instability (Thiel de Bocanegra and Brickman, 2004). There may also be cultural differences in the desirability of reporting psychiatric symptoms that could affect the ethnicity-PTSD relationship (Norris et al, 2001), which we did not explore. We also did not have predisaster data, with much of our data being based on retrospective measures.…”
Section: Discussionmentioning
confidence: 90%
“…That PTSD is a frequent outcome of natural catastrophes has been documented in prior research (e.g., Bronisch et al, 2006, for tsunamis;Norris et al, 2001;Grainger, Levin, AllynByrd, Doctor, & Lee, 1997, for hurricanes;van der Kolk et al, 1996, for volcanoes;Kisac, 2006;Konuk et al, 2006, for earthquakes). Reyes and Elhai (2004) assert that time is precious in post-disaster settings, and immediate intervention is necessary.…”
Section: Discussionmentioning
confidence: 97%
“…suggested that the higher PTSD rate for Puerto Ricans in their study was possibly due to the greater expressiveness of this group compared to Whites. Norris, Perilla, and Murphy (2001) in their study of Whites in Florida and Mexicans in Mexico subjected to similarly devastating hurricanes argue that Hispanics in general more readily acknowledge symptoms than other race/ethnic groups because culturally it is not seen as a personal failing or shortcoming. These speculations offer possible reasons for Puerto Ricans' elevated chances of experiencing a panic attack in the wake of the WTCD.…”
Section: Discussionmentioning
confidence: 99%